NEED ANALYSIS OF SCIENTIFIC-BASED APPROACH WORKSHEET BY USING DISCOVERY LEARNING MODEL FOR SENI BUDAYA AT JUNIOR HIGH SCHOOL - Wisdiarman Wisdiarman; Abdul Hafiz (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2017)
ANALISIS KEBUTUHAN LKS BERBASIS PENDEKATAN SAINTIFIKDENGAN MODEL DISCOVERY LEARNING PADA MATA PELAJARAN SENI BUDAYA DI SMPAbstract The purpose of this research is to: 1) find out the teacher's need for worksheet that can assist the students in art and cultural learning of fine art material; 2) to know the student's need for LKS that can help students in learning art and culture especially fine art material; 3) to know the needs of art and cultural learning of fine art material will worksheet based on scientific approach with discovery learning model. This research used descriptive qualitative method. Subjects in this study were art teacher of culture and grade VII junior high school students in Bukittinggi. Techniques of collecting data were interview, questionnaire and observation. The result of this research are: 1) the teachers of cultural art of junior high school in Bukittinggi need worksheets in the implementation of art and cultural learning in fine art material, 2) students need worksheet in the implementation of art and cultural learning of fine art material and 3) art learning implementation of art material art need LKS based scientific approach with discovery learning model that can help students master the material better.AbstakTujuan dari penelitin ini adalah untuk: 1) mengetahui kebutuhan guru akan LKS yang dapat membantu siswa dalam pembelajaran seni budaya materi seni rupa; 2) mengetahui kebutuhan siswa akan LKS yang dapat membatu siswa dalam pembelajaran seni budaya materi seni rupa; 3) mengetahui kebutuhan pembelajaran  seni budaya materi seni rupa akan LKS  berbasis pendekatan saintifik dengan model discovery learning.  Metode yang  digunakan  dalam  penelitian  ini  adalah  metode  deskriptif  kualitatif. Subjek  dalam  penelitian  ini  adalah  guru seni budaya  dan  siswa  kelas VII SMP di Kota Bukittinggi.  Teknik pengumpulan data adalah wawancara,  penyebaran  angket dan observasi.  Hasil dari penelitian ini adalah:  1)  guru seni budaya SMP Bukittinggi  membutuhkan  LKS  dalam pelaksanaan pembelajaran seni budaya materi seni rupa, 2) siswa membutuhkan LKS dalam pelaksanaan pembelajaran seni budaya materi seni rupa dan 3) pelaksanaan pembelajaran seni budaya materi seni rupa membutuhkan LKS berbasis pendekatan saintifik dengan model discovery learning, sehingga dapat membantu siswa menguasai materi dengan lebih baik. Kata kunci: analisis kebutuhan, pembelajaran seni rupa, LKS berbasis pendekatan saintifik